The evolution of clot strength in critically-ill COVID-19 patients: a prospective observational thromboelastography study - Colette Neethling (BMC, 2021)
Abstract Background Few studies detail the evolution of COVID-19 associated coagulopathy. We performed serial thromboelastography (TEG) and laboratory coagulation studies in 40 critically-ill, mechanically ventilated COVID-19 patients over a 14-day period and analysed differences between 30-day survivors and non-survivors. Methods Single-center prospective, observational study including 40 patients with severe COVID-19 pneumonia admitted to the intensive care unit (ICU) for mechanical ventilation. TEG analysis was performed on days 1, 7 and 14 of ICU admission and laboratory coagulation studies were performed on days 1 and 14. Coagulation variables were evaluated for change over the 14-day observation period. Differences between survivors and non-survivors at 30-days were analysed and compared. Results On admission, TEG maximum amplitude (MA) with heparinase correction was above the upper limit of the reference range in 32 (80%) patients while 33 (82.5%) presented with absent clot lysis at 30 min. The functional fibrinogen MA was also elevated above the upper limit of the reference range in 37 (92.5%) patients. All patients had elevated D-dimer and fibrinogen levels, mildly prolonged prothrombin times (PT), normal platelet counts and normal activated partial thromboplastin times (aPTT). The heparinase MA decreased significantly with time and normalised after 14 days (p = < 0.001) while the increased fibrin contribution to clot strength persisted with time (p = 0.113). No significant differences in TEG analysis were noted between 30-day survivors and non-survivors at all time points. No patients developed disseminated intravascular coagulopathy (DIC) after 14-days, however thrombosis and bleeding were each reported in 3 (7.5%) patients. Conclusion Critically-ill patients with COVID-19 present in a hypercoagulable state characterised by an increased clot strength. This state normalises after 14 days despite a persistently increased fibrin contribution to clot strength. We were unable to demonstrate any significant differences in TEG parameters between 30-day survivors and non-survivors at all time points.